THE Penggunaan Metode Simpleks Terhadap Keuntungan Harian pada Usaha Rumah Makan Viola Batunirwala Di Kota Kalabahi - Damaris Lalang; Landerius Maro; Wehelmina T. Onmay (Fakultas Pertanian, Universitas Timor, 2020)
Mathematics is a tool to simplify the presentation and understanding of problems. Every business actor must do what is called an economic principle, namely that with a little effort or capital it can generate large profits, so that optimization problems arise. The simplex method is an algorithmic procedure that is used to calculate and store a lot of numbers in the initial iterations and for decision making in subsequent iterations. The simplex method is a method commonly used to solve every problem in linear programming where a combination of variables consists or two or more variables. The aim of this research is to optimize daily profit at Viola Batunirwala restaurant. This research is literary by examining journals and books in accordance with the field under study. The steps to optimize daily profit include : (1) Observation, (2) Data Collection, (3) Optimizing daily profit using the simplex method. The results of calculations using the simplex method show that the production applied to the Viola Batunirwala Restaurant is optimal. Profit in one production is Rp. 373.762.